Initial Assessment on Learners’ Need in a Community: Basis for Pre-service Teachers’ Teaching Immersion - Kristoffer Paul C. Obispo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Preservice teachers’ preparation is crucial to the real world of teaching. To prepare teacher education students, field study courses are embedded in the curriculum before the teaching internship. Other preparations such as attendance to seminar/workshop with special topics relevant to the teaching-learning process as well as community immersions are included in the long list of preparations. Community immersion allows a preservice teacher to gain experience that later on will be important in the teaching practice. Such immersion can only be achieved successfully if preparation is done appropriately. In this study, a qualitative needs assessment was performed in one barangay in Olongapo City. An interview with the chair of the committee on education of the barangay was conducted to gather information about the participants and to the barangay’s program for these learners. It revealed that mathematics literacy programs are the most sought after in the locale, which is followed by reading literacy and science learning. Observation and random interviews among the participants were performed to observe and document both the numeracy skills and scientific literacy skills of the participants in the program in this study. The result of the assessment and observation is therefore used to craft a literacy program that will be participated in by learners of the barangay and facilitated by BSED-Science and BSED-Mathematics Pre-service teachers.